2022
DOI: 10.3390/jcm11185456
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Block for Pain Management after Total Hip Arthroplasty: A Retrospective Study with Propensity Score Matching

Abstract: This study aimed to evaluate the effect of a peripheral nerve block (PNB) on immediate postoperative analgesia and the early functional outcomes for patients who underwent total hip arthroplasty (THA). From January 2016 to August 2021, 353 patients who underwent THA were divided into two groups: the patient-controlled analgesia (PCA) group (n = 217) who received only intravenous (IV) analgesia, and others who received IV PCA and PNB (PCA + PNB group) (n = 136). After propensity score matching for age and sex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Peripheral nerve blocks (PNB) have remarkable benefits for immediate postoperative pain control after primary total hip arthroplasty (THA). The analgesic effect of PNB with IV PCA was better than conventional IV PCA alone [3].…”
Section: Incidence Of Painmentioning
confidence: 81%

Postoperative Pain in Orthopedics

Trinidad Castillo García,
Estela Elizabeth Ortega Ponce,
Carolina Martínez Esparza
2023
Topics in Postoperative Pain
“…Peripheral nerve blocks (PNB) have remarkable benefits for immediate postoperative pain control after primary total hip arthroplasty (THA). The analgesic effect of PNB with IV PCA was better than conventional IV PCA alone [3].…”
Section: Incidence Of Painmentioning
confidence: 81%

Postoperative Pain in Orthopedics

Trinidad Castillo García,
Estela Elizabeth Ortega Ponce,
Carolina Martínez Esparza
2023
Topics in Postoperative Pain
“…Many types of peripheral nerve blocks have been developed to minimize perioperative pain and maximize physical function for hip arthroplasty, such as FIB and QLB. [26,27] However, their comparison for pain control is unclear after hip arthroplasty. Our Regarding the sensitivity analysis, significant heterogeneity was seen among the included studies for the pain scores at 12 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The pain relief effect of PNB in THA at early postoperative period is well known, and PNB has been considered an essential component of pain management [15,[22][23][24]. In this study, femoral nerve block, quadratus lumborum block, fascia iliaca compartment block, lateral femoral cutaneous nerve block, and pericapsular nerve group block after THA were performed according to the decision of the anesthesiologist in our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that peripheral nerve block (PNB) after THA has excellent advantages in terms of pain control, as well as in decreasing the risk of various postoperative complications in patients [15][16][17]. There are many methods of PNB that can be applied to THA.…”
Section: Introductionmentioning
confidence: 99%